Fostering social inclusion in digital food system interventions - Steinke, Jonathan; Schumann, Charlotte; Langan, Simon J.; Muller, Anna; Opola, Felix Ouko; Berta Ortiz-Crespo; Etten, Jacob van (2023)
To ensure an equitable digital transformation, deliberate efforts are needed to promote the inclusivity of emerging digital innovations. This short communication outlines challenges and opportunities for considering inclusivity in the design and deployment of digital food system innovations. Drawing on literature and the authors’ experiences within CGIAR, we highlight shortcomings in the digital inclusion discourse. We propose an agenda for enabling researchers and other innovation stakeholders, including donors, to contribute to more inclusive digital innovation. First, a standard concept and procedure is required for assessing the inclusivity of digital services. Second, simple design tools can help researchers effectively consider social inclusion criteria during the design of digital solutions. Lastly, a stronger emphasis on inclusivity is required throughout the research-for-development system. As the importance of digital innovation keeps growing within CGIAR, this article helps researchers and practitioners gain conceptual clarity on the goal of digital inclusion. Concrete suggestions are made for a more equitable, inclusive digital transformation of food systems.